The Influence of Objectivity and Independence on Internal Audit Performance at the Regional Supervision Inspectorate of the North Sulawesi Regional Police - Muslikan, Muslikan; Masengi, Evi Elvira; Dilapanga, Abdul Rahman (Technium Social Sciences Journal, 2022)
The aim of this study is to describe and analyze the objectivity and independence of auditors/examiners on the performance of internal auditors within the North Sulawesi Regional Police Supervision Inspectorate. The method used is a quantitative research method. The results of the research that the researchers obtained were: There is a positive effect of objectivity on the performance of internal auditors. The higher the objectivity of the internal auditors, the higher the performance produced by the internal auditors. Conversely, the lower the objectivity of the internal auditors, the lower the performance produced by the internal auditors. The contribution of objectivity to the performance of internal auditors is 41.9%. There is no effect of independence on the performance of the internal auditors. Due to the results of testing the second hypothesis, the effect of independence on the performance of internal auditors obtained a regression value of 1.955 with a p value of 0.058 (p <0.01) so the second hypothesis was rejected. There is a significant influence simultaneously between objectivity and independence on the performance of internal auditors. Based on the results of the multiple linear regression analysis above, the results obtained from the third hypothesis test between objectivity and independence variables on the performance of the internal auditor ITWASDA POLDA of North Sulawesi obtained an F value of 16.621 (p <0.01), so the third hypothesis is accepted, namely there is a significant influence between interest career and perceptions of career information services on career decision making. The effective contribution of career interest and perceptions of career information services to career decision-making is 47.3% and the remaining 52.7% is influenced by other factors not examined in this study.